Perilaku Menyimpang Mahasiswa dalam Kinerja Akademik di Perguruan Tinggi - Mawarti, Rista Ayu; Hakim, Suparlan Al; Habibi, Muhammad Mujtaba; Pramesti, Lilya Windi; Shofa, Abd. Mu'id Aris; Alfaqi, Mifdal Zusron (Universitas Negeri Malang, 2021)
This study aimed to describe the forms, causes, and efforts to minimize the occurrence of deviant behavior patterns in college students. This study used a qualitative approach with the type of case study research. The main subjects in this study were students of the Pancasila and Citizenship Education Study Program, Faculty of Social Sciences, State University of Malang, who were supported by the involvement of lecturers and teaching staff as supporting informants. Observations, interviews, and documentation were used as procedures for data collection techniques. Data analysis was carried out through several stages, including data reduction, data presentation, and drawing conclusions. The results of the study showed that there were three forms of student deviant behavior in academic performance, namely the fabrication of research proposals in the Pancasila and Citizenship Education Seminar, falsification of assignments for the Personality Psychology course, and plagiarism of Public Policy course assignments. The causes of this deviant behavior were laziness, lack of time management, and lack of learning discipline. The two-way communication process through deliberation and delivery of commitments to improve behavior was chosen as an effort to minimize the occurrence of deviant behavior in academic performance in universities.